Karakteristik Petani dan Kontribusi Konsep Agrowisata terhadap Pendapatan Petani Jeruk di Kabupaten Karo - LITNA NURJANNAH GINTING; WILDANI LUBIS; DIAN RETNO INTAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Characteristics of Citrus Farmers and Agro-Tourism Contribution in Enhancing Farmers’ Income in Karo District Agro-tourism is one of the tourism activities that utilize the potential of agriculture as tourist attractions such as natural scenery or agricultural production activities. U-pick is an agro-tourism concept that adopts by the citrus farmers in Karo district. The visitors will get the experience to pick the fruit by themselves. On the other hand, Farmers can sell their fruits at a higher price than sold to local agents. The purpose of this research is to ascertain the characteristics of farmers who implement agro-tourism concepts and analyze the contribution of agro-tourism to the citrus farmers’ income. This research used descriptive and economic analysis methods. The results show that the farmers were in productive age with a good education. This business is a family scale, the farmer experienced in farming but relatively new in implementing the agro-tourism concept. The location of the farm is on the roadside so it is accessible by the tourist. The U-pick concept gives a positive effect on the revenue and income of the farmers. The contribution of this concept to the total income of citrus farmers is 29,92%.